Appearance comparison, fear of negative evaluation, and attitudes toward cosmetic surgery in adults - Jameel, Rabia; Jahangir, Sahrash; Mah Noor (Journal of the Pakistan Medical Association, 2026)
Objective: To investigate the connection between appearance comparison, fear of negative evaluation, and attitude towards cosmetic surgery, and to find out the mediating role of fear of negative evaluation. Method: The cross-sectional study was conducted at the Riphah Institute of Clinical and Professional Psychology, Riphah International University, Lahore, from April to November 2022, and comprised adults aged 19-40 years of both genders from across the country. Data was collected online using a self-designed demographic sheet, the Physical Appearance Comparison Scale, the Acceptance of Cosmetic Surgery Scale, and the Fear of Negative Appearance Evaluation Scale. Data was analysed using SPSS 21. Results: Of the 405 participants, 337(83.2%) were females and 68(16.8%) were males. The overall mean age was 27.17±5.450 years. Appearance comparison related to body image was positively linked with fear of negative evaluation and attitudes towards cosmetic surgery (p<0.05), while appearance comparison related to body image and fear of negative evaluations significantly predicted attitudes towards cosmetic surgery (p<0.005). Moreover, fear of negative evaluation significantly mediated between appearance comparison related to body image and attitude towards cosmetic surgery (p<0.000). Conclusion: Appearance comparison related to body image was found to be significantly associated with fear of negative evaluation and attitude towards cosmetic surgery. Key Words: Body image, Attitudes, Cosmetic surgery, Fear of negative evaluation.